Análise Metabolômica de Peperomia obtusifolia (L.) A. Dietr. - Souto, Augusto Lopes (2015)
The species Peperomia obtusifolia (L.) A. Dietr, which belongs to the Piperaceae family, is a well-known plant, distributed from Mexico to South America. Previous phytochemical studies demonstrated the presence of compounds from several classes, such as: lignans, flavonoids, amides, phenolic compounds and chromenes, which demonstrated interesting biological activities. This work describes the metabolomic analysis of Peperomia obtusifolia, which study in real time, the metabolism of this species in many kinds of scenarios. However, to accomplish this study, firstly it was developed a standard protocol, capable of preparing the samples in a reproducible way, enabling the following metabolomic studies to generate reliable results. Later, it was conducted the metabolomic study of Peperomia obtusifolia and its varieties, by fingerprinting analysis, in order to characterize the metabolomic profiles of each one of them. Furthermore, it was also evaluated the behavior of the species against the stress induced by the herbivory of Monoplatus sp. In general, the analyzes were conducted by NMR of 1H (which the data was interpreted by PCA), mass spectrometry, HPLC, GC and its hyphenated techniques. As a result, it was found that, despite the fact that the Peperomia obtusifolia varieties belong to the same species, they had different metabolomes. Regarding the study of the biotic stress against the plant, changes were detected on the metabolomic profile of the attacked plants, indicating a response against the herbivore attack. As a major result of this research, it can be highlighted the fact that the same changes were also detected on the metabolome of the intact plants closed to the attacked ones, indicating a sort of interplant communication by volatile compounds, capable to induce the neighborhood yet not attacked, to be prepared for an imminent attack, giving them a better chance of survival.